Evaluating the biomechanical performance of Ti6Al4V volar plates in patients with distal radius fractures - Li, Hua; Wang, Daofeng; Zhang, Wupeng; Xu, Cheng; Xiong, Dou; Li, Jiantao; Zhang, Licheng; Tang, Peifu (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose This study aimed to investigate the biomechanical performance of three Ti6Al4V volar plates with the latest designs using a finite element model. Methods An AO type 23-A3 distal radius fracture and the models of T plate (2.4mm LCP Volar Distal Radius Plate), V plate (2.4mm LCP Two-Column Volar Distal Radius Plate) and π Plate (2.4mm Volar Rim Distal Radius Plate) (all from Depuy Synthes, West Chester, PA, USA, Ti6Al4V) were built in 3D-matic software. After assembling the internal fixation and fractures, we imported these models into the finite element analysis software (ABAQUS). An axial loading of 100N was added to the distal end of each model. The displacements of total models and implants, the principal strains and the von Mises stresses in the plates were calculated and compared to capture the biomechanical features of the three plates. Results The T plate, V plate and π plate represented a model displacement of 0.8414mm, 1.134mm and 1.936mm, respectively. The T plate was with the implant displacement of 0.7576mm, followed by the V plate (0.8802mm) and the π plate (1.545mm). The T plate had the smallest principal strain of 0.23%, the V plate showed an intermediate level of 0.28%, and the π plate had a value of 0.72%. The least peak von Mises stress was observed in the V plate with 263.6MPa, and this value was 435.6MPa and 1050MPa in the T plate and π plate, respectively. Conclusion The biomechanical features of three Ti6Al4V volar locking plates in an AO type 23-A3 fracture were described in our analysis. The T plate and the V plate showed similar biomechanical performance while the π plate represented worse performance than the other two plates.